Response Of Cauliflower To Nitrogen Fixing Biofertilizer And Graded Levels Of Nitrogen - Bashyal, Lila Nath (Journal of Agriculture and Environment, 2013)
A field experiment was carried out at Rampur, Chitwan, Nepal during September, 2007 to February, 2008 to assess the response of cauliflower (Brassica oleracea L. var. botrytis cv. Kathmandu Local) to biofertilizer containing free living nitrogen fixing bacteria Azospirillum and Azotobacter and different levels of nitrogen. The experiment was laid out in factorial Randomized Complete Block Design consisting of 10 treatments (nitrogen 0, 30, 60, 90 and 120 kg ha–1 alone and in combinations of 2 kg of the nitrogen fixing biofertilizer) arranged in 5 × 2 complete factorial with 3 replications. Application of nitrogen along with the biofertilizer significantly increased morphological, yield and quality characters as compared to application of nitrogen without biofertilizer. The maximum stem height, stem diameter, highest curd height, curd diameter, fresh curd weight and curd yield were recorded at 120 kg nitrogen and 2 kg biofertilizer ha–1. Cauliflower curd yield obtained at 120 kg nitrogen ha–1 did not significantly differ with the curd yield recorded at 60 kg nitrogen and 2 kg biofertilizer ha–1. The earliest days to curd initiation and maturity were recorded at 30 kg nitrogen and 2 kg biofertilizer ha–1. The highest vitamin C content of curds and the most attractive curd color were recorded at 60 kg nitrogen and 2 kg biofertilizer ha–1, while the appearance and over all acceptability were recorded at 120 kg nitrogen and 2 kg biofertilizer ha–1. The finding demonstrated a saving of 60 kg nitrogen ha–1 without significantly affecting yield. The Journal of Agriculture and Environment Vol:12, Jun.2011, Page 41-50 DOI: http://dx.doi.org/10.3126/aej.v12i0.7562